An ancient olive tree in the garden. Mapping the deep history of land use from a single image - Vincenza Ferrara; Anders Wästfelt (Geocarto International)
Landscapes with a deep history of land use are the legacy of millennial interactions between ecological, social and cultural elements, which can be investigated to obtain new knowledge about our present-day ecosystems. This paper presents the application of a supervised contextual post-classification technique to extract, from a single orthoimage, geospatial objects (classes) representing different temporalities of the same land use in a historical landscape. With a rural area of Sicily as case study and its century-old olive trees as geospatial ‘control points’, we analyse the degree of category similarity between historica lly contingent classes of the same land use. We map and interpret from present space their dynamics of change and persistence over time, cross-validating our results with evidence from local plant microfossils (phytoliths) analysis. We demonstrate how Earth observation products and contextual geospatial analysis are multidimensional sources of information enriching our understanding of past-present landscapes and their biocultural heritage.